2019
DOI: 10.1177/0959683619862033
|View full text |Cite
|
Sign up to set email alerts
|

Plant landscape reconstruction above the current timberline at the Monte Cimone and Corno alle Scale mountain areas (Northern Apennines, Italy) during the Late Holocene: The evidence from soil charcoal

Abstract: This paper presents the first pedoanthracological study carried out on two mountains of the Northern Apennines, Monte Cimone, and Corno alle Scale, where the results provided new palaeoenvironmental data. The pedoantracological sampling followed an elevation gradient from the current timberline to the highest possible elevation, also adapted to the geomorphological characteristics of the study areas. Based on radiocarbon datings (16 at Monte Cimone and 9 at Corno alle Scale), the soil charcoal fragments provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…The most likely explanation of the low F. sylvatica treeline at the southern exposure (Figure 2 ) in the Apennines lies in the complex interaction between climate (e.g., freezing temperature, short growing season, and summer drought) and past human disturbance that shaped the actual treeline over the centuries, which goes beyond the differences imposed by the slope exposure itself. To date, concrete evidence of anthropogenic impact on treeline elevation along the Apennine chain emerged (Benatti et al, 2019 ; Brown et al, 2013 ; Compostella & Caccianiga, 2017 ). In the subalpine belt, centuries of logging and coppicing promoted vegetative reproduction from stump sprouting rather than clonal layering from basal branches (Saulino et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most likely explanation of the low F. sylvatica treeline at the southern exposure (Figure 2 ) in the Apennines lies in the complex interaction between climate (e.g., freezing temperature, short growing season, and summer drought) and past human disturbance that shaped the actual treeline over the centuries, which goes beyond the differences imposed by the slope exposure itself. To date, concrete evidence of anthropogenic impact on treeline elevation along the Apennine chain emerged (Benatti et al, 2019 ; Brown et al, 2013 ; Compostella & Caccianiga, 2017 ). In the subalpine belt, centuries of logging and coppicing promoted vegetative reproduction from stump sprouting rather than clonal layering from basal branches (Saulino et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with a contemporary study of Batllori and Gutiérrez ( 2008 ) suggesting that treeline dynamics of Pinus uncinata in the Pyrenees have been widely affected by local anthropogenic activities. In addition, Bonanomi et al ( 2018 ) reported that the present Italian Apennines' Fagus sylvatica treeline is several hundred meters below its climatic potential because of widespread land‐use change, as confirmed from several paleoecological findings (e.g., Benatti et al, 2019 ; Brown et al, 2013 ). Therefore, any hypotheses of treeline dynamics, at local than global scales, in response to climate warming should at least consider the complex interaction among thermal requirements, physiological stressors, and disturbance regime, especially in mountains with a long history of human exploitation (Ameztegui et al, 2016 ).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Each pit occupied an area of approximately 0.3 m 2 . The sampling was carried out by stripping the soil in increments of 5-10 cm, starting from the surface and working down to the bedrock, imitating archeological methodology (Bal and Garcia-Álvarez, 2022;Benatti et al, 2019). About 5 kg of wet soil were collected from each sampling level.…”
Section: Sampling Strategymentioning
confidence: 99%
“…Since its range distribution is confined below the climatic treeline, F. sylvatica's upper elevation limit across the Apennines is more properly a species range limit (Körner, 2021), where past anthropogenic disturbances (Bonanomi et al, 2018) are prevailed on the eco-physiological limitations to the growth processes commonly related to the freezing tolerance (Körner, 2012a). Apennine beech forests are also known to be prominent examples of human-shaped forest landscapes, where the forest cover was manipulated starting from the late Holocene (Compostella et al, 2013;Benatti et al, 2019;Morales-Molino et al, 2021). For centuries, along the Italian Apennines' mountain belt (from a latitude of 38 • to 44 • N), silviculture has been involved mostly in coppicing with the removal of the larger shoots from the stools (Coppini and Hermanin, 2007).…”
Section: Introductionmentioning
confidence: 99%